GUARDIANS OF GOVERNANCE: IMPLEMENTASI GOOD CORPORATE GOVERNANCE DALAM PELAYANAN PUBLIK PADA PERUMDA AIR MINUM DUASUDARA KOTA BITUNG - Mifta, Lanika; Novia R. Yanis; Rusni Malahedi; Nabila A. Usman; Michelle P.C. Pangemanan; Monika I. K. Sukatno; Feiby N. Wantah (STIE PGRI Dewantara Jombang, 2024)
This study aims to analyze the implementation of Good Corporate Governance (GCG) principles and their impact on the effectiveness of public services at Perumda Air Minum Dua Sudara, Bitung City. The principles of GCG—transparency, accountability, responsibility, independency, and fairness—serve as the foundation for creating clean, professional, and community-oriented public management. The research employs a qualitative descriptive approach, focusing on understanding how GCG principles are applied within the company and how they influence service quality. Data were collected through interviews, observation, and documentation. The findings indicate that Perumda Dua Sudara has implemented GCG principles consistently through transparent information disclosure, financial accountability, social responsibility programs, independent decision-making, and fair service distribution. This implementation has improved service efficiency, responsiveness, and public trust. However, several challenges remain, including public resistance to tariff adjustments, limited understanding of GCG among employees, and negative media perceptions. Despite these challenges, GCG application has proven to enhance the company’s operational performance and service effectiveness. The study concludes that consistent GCG implementation is crucial to strengthening governance, increasing customer satisfaction, and ensuring sustainable public service performance.